Reduced risk of hepatocellular carcinoma by achieving a subcirrhotic liver stiffness through antiviral agents in hepatitis B virus‐related advanced fibrosis or cirrhosis - Kim, Byung Seok; Seo, Yeon Seok; Kim, Young Seok; Lee, Chang Hyeong; Lee, Han Ah; Um, Soon Ho; Yoo, Jeong‐Ju; Kim, Sang Gyune; Suh, Sang Jun; Jung, Young Kul; Ahn, Sang Hoon; Han, Kwang‐Hyub; et al. (Journal of Gastroenterology and Hepatology, 2018)
Background and Aim A subcirrhotic range of liver stiffness (sc‐LS), assessed by transient elastography, is associated with better outcomes in patients with chronic hepatitis B (CHB). We investigated whether the achievement of sc‐LS by antiviral therapy (AVT) reduced the risk of developing hepatocellular carcinoma (HCC) in patients with CHB‐related advanced fibrosis or cirrhosis. Methods In total, 209 patients with CHB‐related advanced fibrosis or cirrhosis, who received paired transient elastography examinations during AVT between 2007 and 2012, were enrolled. The cut‐off LS value for ultrasonographic cirrhosis was defined as 11.6 kPa. Results The median age of the study population was 51 years, with males predominating (n = 138, 66.0%). The median LS value at enrollment was 14.1 kPa (interquartile range: 9.5–24.1 kPa). After 2 years of AVT, 140 (67.0%) patients achieved sc‐LS. During the study period, 28 (13.4%) patients developed HCC after 2 years of AVT. On multivariate analysis, the achievement of sc‐LS after AVT was independently associated with a decreased risk of HCC development (hazard ratio [HR] = 0.485, P = 0.047), whereas older age (HR = 1.071) and male gender (HR = 3.704) were independently associated with an increased HCC risk (both P < 0.05). Patients with a cirrhotic range of LS value after 2 years of AVT were at a higher risk of HCC development than those with sc‐LS (log‐rank test, P = 0.020). Conclusions The achievement of sc‐LS after AVT can reduce the risk of HCC development in patients with CHB, even when advanced fibrosis or cirrhosis is apparent on starting AVT.